Parental burnout at different stages of parenthood: Links with temperament, Big Five traits, and parental identity - Piotrowski, Konrad; Bojanowska, Agnieszka; Szczygieł, Dorota; Mikolajczak, Moïra; Roskam, Isabelle (Frontiers in Psychology, 2023)
The study aimed to analyze the links between traits from different levels of personality organization and parental burnout. To answer the research questions, a cross-sectional study was conducted with 1471 parents aged 19 to 45 years (mean age 35.30, SD = 5.98). The results showed that the severity of parental burnout was linked to traits ranging from biologically determined temperament traits to basic personality traits to a sense of parental identity. More specifically, we found higher burnout among parents who have difficulty shifting between tasks and coping with strong stimulation, low emotional stability and conscientiousness, and low identification with the parental role. We also found that certain personality traits were more strongly associated with parental burnout among those who had children in early childhood or preschool period (under the age of seven) than those in later stages of parenthood. The study contributes knowledge about the personality correlates of parental burnout and the role of personality at different stages of parenthood.